Variation in Physician Reimbursement for Endoscopy across Canada - Lee S Roth; Paul C Adams (Canadian Journal of Gastroenterology)
BACKGROUND: Endoscopy accounts for a significant proportion of income for physicians practicing gastroenterology. Fees are set provincially, and the consistency with regard to compensation for colonoscopy and gastroscopy across the provinces has yet to be established.